Academic Emotions and Regulation Strategies: Interaction with Higher Education Dropout Ideation - Daniel Enguídanos; Javier Aroztegui; Manuel Iglesias-Soilán; Irene Sánchez-; Juan Fernández (MDPI AG, 2023)
(1) Introduction: This article addresses the relationship between students' emotional experiences-mediated by their regulation strategies-and their intention of dropping out. (2) Materials and Methods: An ad hoc questionnaire was designed based on Pekrun's Control-Value Theory of Achievement Emotions focusing on three different settings (study, classroom, and exam). Data were collected from 2183 university students. Descriptive, frequency, and correlation analysis were conducted. Also, linear regression analyses and scatter plots were performed. A comparative regression analysis was used with the aim of facilitating the understanding of the mediating effect of emotional regulation strategies. (3) Results: Academic emotions were found to have a significant impact on dropout ideation. The effects of emotional regulation strategies as significant moderators in this relationship were observed, exhibiting variations depending on the context. (4) Discussion: Dropout ideation escalates in the presence of elevated levels of unpleasant emotions and diminished levels of pleasant emotions. The utility of possessing effective emotional regulation strategies becomes evident in mitigating dropout ideation during emotionally challenging academic situations.